2020
DOI: 10.1139/cjpp-2019-0352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of somatostatin, curcumin, and quercetin on the fatty acid profile of breast cancer cell membranes

Abstract: Breast cancer is a worldwide commonly found malignancy in women and effective treatment is regarded as a huge clinical challenge even in the presence of several treatment options. Extensive literature is available demonstrating polyphenols as phytopharmaceutical anticancer agents. Among the polyphenols, quercetin and curcumin have been reported to have a strong potential against breast cancer. However, so far, no comprehensive study has been performed to demonstrate the anticarcinogenic effects of curcumin, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…As regards the n-3 fatty acids pathway, no variation was observed. Hanikoglu A. et al found differences in the reorganization of fatty acids in cell membranes of two different breast cancer cell lines, MCF-7 and MDA-MB231, after treatment with somatostatin, curcumin, and quercetin, alone or in combination [ 14 ]. Cancer cells, according to the degree of differentiation, behave differently to treatment with drugs and/or natural compounds, and this feature could explain the different response of SW480 to treatment with GSEs, with respect to Caco2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the n-3 fatty acids pathway, no variation was observed. Hanikoglu A. et al found differences in the reorganization of fatty acids in cell membranes of two different breast cancer cell lines, MCF-7 and MDA-MB231, after treatment with somatostatin, curcumin, and quercetin, alone or in combination [ 14 ]. Cancer cells, according to the degree of differentiation, behave differently to treatment with drugs and/or natural compounds, and this feature could explain the different response of SW480 to treatment with GSEs, with respect to Caco2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are several mechanisms of action through which grape polyphenols are able to inhibit the invasion and progression of metastasis [ 11 , 12 , 13 ]. These natural compounds can act on the structural components of the cytoskeleton, on cellular adhesions, and on the composition of the membrane fatty acids [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported relatively higher doses or longer durations of exposure for both compounds in order to obtain a significant cytotoxic activity on breast cancer cells (Maurya & Vinayak 2019, Morais-Santos et al 2013; however, some studies have reported a relatively lower dose for quercetin. For instance, Hanikoglu et al 2020 reported the IC 50 value of quercetin as 73.63 µM and Niazvand et al 2019 reported it as 73.8 µM, both after 24 h of incubation (Hanikoglu et al 2020, Niazvand et al 2019. Overall data indicate that the doses we have used in our study are within the spectrum of doses used in the previous and/or recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase inhibition by flavonoids has been reported and associated with modulation of cell growth and promotion of apoptosis [63]. Quercetin led MDA-MB-231 and MCF-7 cells to EGFR reduction and this signaling promoted fatty acid alterations, including fatty acid isomerization and free radicals production [64].…”
Section: Flavonolsmentioning
confidence: 99%